Changes in QRS Area and QRS Duration After Cardiac Resynchronization Therapy Predict Cardiac Mortality, Heart Failure Hospitalizations, and Ventricular Arrhythmias. Issue 21 (5th November 2019) - Okafor, Osita; Zegard, Abbasin; van Dam, Peter; Stegemann, Berthold; Qiu, Tian; Marshall, Howard; Leyva, Francisco
Abstract : Background: Predicting clinical outcomes after cardiac resynchronization therapy (CRT) and its optimization remain a challenge. We sought to determine whether pre‐ and postimplantation QRS area (QRSarea ) predict clinical outcomes after CRT. Methods and Results: In this retrospective study, QRSarea, derived from pre‐ and postimplantation vectorcardiography, were assessed in relation to the primary end point of cardiac mortality after CRT with or without defibrillation. Other end points included total mortality, total mortality or heart failure (HF) hospitalization, total mortality or major adverse cardiac events, and the arrhythmic end point of sudden cardiac death or ventricular arrhythmias with or without a shock. In patients (n=380, age 72.0±12.4 years, 68.7% male) undergoing CRT over 7.7 years (median follow‐up: 3.8 years [interquartile range 2.3–5.3]), preimplantation QRSarea ≥102 μVs predicted cardiac mortality (HR: 0.36; P <0.001), independent of QRS duration (QRSd) and morphology ( P <0.001). A QRSarea reduction ≥45 μVs after CRT predicted cardiac mortality (HR: 0.19), total mortality (HR: 0.50), total mortality or heart failure hospitalization (HR: 0.44), total mortality or major adverse cardiac events (HR: 0.43) (all P <0.001) and the arrhythmic end point (HR: 0.26; P <0.001). A concomitant reduction in QRSarea and QRSd was associated with the lowest risk of cardiac mortality and the arrhythmic end point (both HR: 0.12, P <0.001). Conclusions: Pre‐implantation QRSarea, derived from vectorcardiography, was superior to QRSd and QRS morphology in predicting cardiac mortality after CRT. A postimplant reduction in both QRSarea and QRSd was associated with the best outcomes, including the arrhythmic end point.